Influence of Sugars, Modified Starches and Hydrocolloids Addition on Colour and Thermal Properties of Raspberry Cream Fillings - Pichler Anita; Pozderović Andrija; Moslavac Tihomir; Popović Kristina (Polish Journal of Food and Nutrition Sciences)
This paper deals with the influence of the addition of sugars (sucrose, fructose and trehalose), modified starches (tapioca or waxy maize starch) and hydrocolloids (karaya or guar gum) on colour and thermal properties of raspberry cream fillings. In addition, the influence of the above-mentioned additives on the colour and thermal properties of raspberry cream fillings stored at room temperature over a period of 8 and 16 months was investigated. Results showed that the highest anthocyanin content and total phenolic content were detected in raspberry cream filling prepared with sucrose and trehalose in combination with guar gum. During storage, after 8 and 16 months at room temperature, anthocyanin content and total phenolic content decreased. Results also showed that the kind of sugar and added modified starches or hydrocolloids influenced the thermal properties of cream fillings. During storage, a decrease was observed in both freezing temperature as well as enthalpy of cream fillings.